Developing next-generation distributed applications with QoS enabled DPE middleware. - Schmidt, D.C.
This article describes how recent advances in distributed object computing middleware are enabling the creation of common quality-of-service capabilities that support next-generation distributed applications. DOC middleware helps to simplify and coordinate applications in order to leverage the underlying network and end-system QoS architectures more effectively. This article also describes a QoS-enabled middleware framework used to customize the CORBA audio/video streaming service for applications on multiple operating system platforms
Keywords: CORBA audio/video streaming service; QoS enabled DPE middleware; Common quality-of-service capabilities; Distributed object computing middleware; End-system QoS architectures; Multiple operating system platforms; Next-generation distributed applications